The Ecranisation of Ratih Kumalas Novel Gadis Kretek into the Film Gadis Kretek Directed by Kamila Andini and Ifa Isfansyah - Purnomo Aji; Onok Yayang Pamungkas (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This article aims to examine a literary work that has been adapted into a film through the perspective of ekranisasi as proposed by Pamusuk Eneste. This study employs a qualitative research method. The research data were collected using a note-taking reading technique and data triangulation to ensure data validity. The data consist of excerpts of dialogue, plot elements, and narration from the film Gadis Kretek, directed by Andini and Isfansyah, as the primary source. Meanwhile, the novel Gadis Kretek by Ratih Kumala serves as the comparative source in this study. Ekranisasi encompasses three main processes: reduction, addition, and variation. These three stages form the basis for adapting and reconstructing the storyline to meet the demands of film production without altering the original message of the literary work. The implications of these findings provide insights into the process of ekranisasi in literary works adapted into films, indicating that differences in storyline or narrative ideas between a film and its source novel arise due to certain reasons, limitations, and other influencing factors in the adaptation process.